Dangdut Songs as Soundtracks for Content on TikTok - Pattiruhu, Misael Juda Alexander; Suharto, Suharto (Universitas Negeri Semarang, 2024)
This study aims to investigate how dangdut songs are used as background music for content on the TikTok application. This study employed descriptive qualitative method to examine the popularity of five selected dangdut koplo songs among its content creators. Data collection techniques involved direct documentation of available data within the application. The findings indicate that TikTok plays a significant role in shaping trends in content types and popularizing songs used as background music. Songs such as